2019
DOI: 10.1080/13668803.2019.1608158
|View full text |Cite
|
Sign up to set email alerts
|

The influence of perceived job flexibility and spousal support on the marital satisfaction of parents of children with special needs

Abstract: Parents of children with special needs can experience more stress in their marriage than parents of children without special needs. Previous work has focused on the child as a major influence for the marital relationship, however this research sought to examine less commonly discussed factors that influence marital satisfaction for these parents. Perceived job flexibility and perceived spousal support in parenting were targeted as potential influencers. A mediation model was attempted to explain the mediating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 84 publications
(183 reference statements)
0
5
0
Order By: Relevance
“…One article (4%; Goldberg et al, 2010) framed the study within the ABCX model in combination with Bronfenbrenner’s (1992) ecological theory, and one article applied Conger’s family stress model in combination with STM (Mitchell et al, 2015). Some papers ( n = 6, 21%) did not include any of the family stress, dyadic coping, or support theories (see Perlowski & Wright, 2021 as an example). These studies referred to Lazarus and Folkman’s (1984) individual stress theory, Bronfenbrenner’s (1992) ecological model, life course theory (Giele & Elder, 1998), Acitelli’s (1992) relationship awareness, and social capital (Coleman, 1990).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One article (4%; Goldberg et al, 2010) framed the study within the ABCX model in combination with Bronfenbrenner’s (1992) ecological theory, and one article applied Conger’s family stress model in combination with STM (Mitchell et al, 2015). Some papers ( n = 6, 21%) did not include any of the family stress, dyadic coping, or support theories (see Perlowski & Wright, 2021 as an example). These studies referred to Lazarus and Folkman’s (1984) individual stress theory, Bronfenbrenner’s (1992) ecological model, life course theory (Giele & Elder, 1998), Acitelli’s (1992) relationship awareness, and social capital (Coleman, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Most articles ( n = 12; 43%) referred to general support/coping, nine (32%) examined this specific to one identity (e.g., perceived spousal support in parenting; Perlowski & Wright, 2021), and seven (25%) referred to coping or support related to multiple interacting identities (e.g., spousal support with parenting and homecare for working mothers; Dickson, 2020). Notably, three of the seven articles (11%) focusing on partner support or dyadic coping used qualitative methodology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the finding of deaf participants experiencing parental separation or divorce in childhood is supported by the literature. The birth of a child with disabilities can be stressful and impact the marital and family relationships (Chowdhury, 2018;Perlowski & Wright, 2019;Shahrier, et al, 2016). Diagnosis, severity of the disorder, parental coping strategies, resources, and community support can impact the degree to which a marriage can be sustained.…”
Section: Are There Significant Differences Between Deaf and Hearing P...mentioning
confidence: 99%
“…Thus, we found that Russian scholars pay more attention to the topic "satisfaction with parenting". In these studies, related to satisfaction with parenting, scholars discussed more key words such as: family structure (Rogers and White 1998), parenting pressure (Carey et al 2009;Sevastyanova 202), parental responsibility (Henderson et al 2016), marital satisfaction (Perlowski et al 2019;Malenova and Borovikova 2008), life satisfaction (Mahmoud et al 2021).…”
Section: Introductionmentioning
confidence: 99%